Spot analyses of serum neopterin, tryptophan and kynurenine levels in a random group of blood donor population - Ünüvar, Songül Ü.; Gi?rgi?n, Gözde; Palabıyık, Şaziye Sezin; Karaagac, Tülay; Özcebe, Osman Ilhami; Şahin, Gönül; Baydar, Terken (Walter de Gruyter GmbH, 2013)
In transfusions, safety measures are used for the health of both receivers and donors. In this regard, early and sensitive markers are strongly needed. The aim of this study was to evaluate neopterin profile and tryptophan degradation in a group of Turkish blood donors. The effect of age, gender, blood type and Rh factor were also assessed. Neopterin was measured by ELISA kits. Serum tryptophan and kynurenine were determined by high performance liquid chromatography. Kynurenine/tryptophan (kyn/ trp) was calculated to estimate tryptophan degradation. Tryptophan, kynurenine and kyn/trp levels were found to be higher in males compared with females (all p < 0.05). Neopterin and kynurenine levels tended to increase with age in age subgroups (all p < 0.05). On the contrary, smoking, Rh factor and blood types were all observed to have no effect on measured parameters (all p ? 0.05). In routine analysis, early and reliable biomarkers are needed. In parallel with current markers, neopterin can be used to select safe donors and to maintain the safety of transfusion. In the face of our results, we recommend that donations with neopterin levels above 19 nmol/L should be excluded from the program because increased neopterin levels indicate activation of the cellular immune system. © 2013 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: 3-dioxigenase; Blood bank; Indoleamine-2; Kynurenine; Neopterin; Tryptophan